OPTIMAL RISK-BASED DESIGN OF CHAO PHRAYA RIVER FLOOD CONTROL SYSTEM FOR BANGKOK - T. Tingsanchali; T. Kitpaisalsakul (International Association of Lowland Technology, 1999)
Risk-based design is a design approach developed for quantifying the probability of failure and the expected annual damage cost of a structural system subject to variations of load such as the river flood level and of resistance such as the strength of flood protection dikes. The approach considers the joint probability density function of the load and the resistance in the computation of the probability of failure and the expected annual damage cost. In this study, an optimal risk-based design procedure of a flood control system is developed. The design approach is a computational framework using four relevant techniques, namely flood flow simulation analysis, coincident flood frequency analysis, load-resistance analysis and optimization of risk-based design. It is applied to determine the optimal capacity of the flood control system for Bangkok based on a maximum net benefit.